Plexiform Myofibroblastoma: Clinicopathologic Analysis of 36 Cases of a Distinctive Benign Tumor of Soft Tissue Affecting Mainly Children and Young Adults. (November 2020) - Papke, David J.; Al-Ibraheemi, Alyaa; Fletcher, Christopher D.M.
Abstract : The spectrum of benign superficial fibroblastic/myofibroblastic tumors continues to expand and includes entities such as plexiform fibrohistiocytic tumor, dermatomyofibroma and fibroblastic connective tissue nevus. Here, we describe a seemingly distinctive group of lesions which we have labeled "plexiform myofibroblastoma" (PM). PM is a rare superficial mesenchymal tumor of fibroblastic/myofibroblastic lineage that predominantly occurs in children and young adults. Thirty-six cases from the consultation archives of one of the authors have been studied to characterize the clinicopathologic characteristics of PM. 19 patients (53%) were female and 17 were male, with age at presentation ranging from congenital (2 cases) to 50 years of age (median: 9.5 y). Three patients had multiple lesions. Males tended to develop tumors during childhood (median: 2 y; range: congenital—37 y), while in females the age distribution was relatively uniform from childhood through adulthood (median age: 25 y; range: 4 mo to 50 y). Most tumors occurred in truncal locations (25/40), including the back (11), anterolateral chest wall (4), axilla (4), abdominal wall (4), perineum (1) and suprapubic region (1). Other tumor sites were the neck (10/40), occiput (2), lower extremity (2) and breast (1). The average greatest dimension was 2.7±1.7 cm (range: 0.6 to 8 cm). Three male patients, 2 of whom were brothers, presented between 6 months and 1 year of age with multiple lesions variably involving the back, occiput and axillae; these lesions spontaneously regressed after being present for about 2 years, with no evidence of recurrence at a mean follow-up of 11.4±3.2 years. Histologically, PM was composed of plexiform fascicles of fibroblastic/myofibroblastic spindle cells that ramify through the subcutis and reticular dermis. The bland neoplastic cells had indistinct cell borders, palely eosinophilic cytoplasm and ovoid or tapered nuclei. There was no histiocytoid component in any case, and no cases contained osteoclast-like giant cells. Twelve of thirty-four (35%) reviewed cases showed at least focal keloidal hyalinization, 6/34 (18%) contained somewhat fasciitis-like areas and 6/34 (18%) contained focal myxoid stroma. Immunohistochemical studies were positive for SMA (27/32 cases), desmin (9/21) and CD34 (13/24) and negative for β-catenin (0/14) and S-100 (0/22). EMA was weakly positive in 2/15 cases. An FGFR2 M535L tyrosine kinase domain variant of unknown significance was detected in 1/7 sequenced cases, and no somatic alterations, copy number alterations or gene fusions were detected in the other 6. Clinical follow-up data were available for 16/36 patients (44%; median duration: 5.5 y). Although most excisions had positive margins (11/16), only 1 patient developed a local recurrence 4 years after initial excision. No tumors metastasized. PM is a benign tumor with characteristic histology, epidemiology and anatomic site distribution. Because PM rarely recurs, a watchful waiting approach would be reasonable for lesions excised with positive margins. Abstract : Supplemental Digital Content is available in the text.